2004
DOI: 10.1007/s00113-004-0757-3
|View full text |Cite
|
Sign up to set email alerts
|

Entwicklung eines Fragebogens basierend auf dem Constant-Murely-Score zur Selbstevaluation der Schulterfunktion durch den Patienten

Abstract: The aim was to develop a German questionnaire for self-assessment of shoulder function equivalent to the Constant-Score (CS). To evaluate the retest reliability, the CS questionnaire was completed twice within 1 week by 47 patients prior to shoulder surgery. For validation the CS was assessed by the physician after the second self-test. The medium selectivity of the CS questionnaire at hospital admission was 0.47, the medium item difficulty 0.40, the test-retest reliability 0.675 ( p=0.000), the internal consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 19 publications
1
26
0
3
Order By: Relevance
“…Moreover, self-assessment questionnaires require a minimal setup and can be completed by mail making them inexpensive [12]. Furthermore, this eliminates the well-recognized examiner observation or selection bias of physicians rating the patients they treated before much better than other physicians or patients themselves [19]. Finally multiple studies have clearly demonstrated that the evaluation by self-assessment questionnaires is highly reliable, valid and responsive [1,12,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, self-assessment questionnaires require a minimal setup and can be completed by mail making them inexpensive [12]. Furthermore, this eliminates the well-recognized examiner observation or selection bias of physicians rating the patients they treated before much better than other physicians or patients themselves [19]. Finally multiple studies have clearly demonstrated that the evaluation by self-assessment questionnaires is highly reliable, valid and responsive [1,12,20].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, performing clinical studies is time consuming, expensive and a logistical challenge, especially when physical presence of the patient is required [3-5,16,19]. In addition, many procedures are performed on outpatients in centers far away from the home of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Shoulder function was ascertained in all patients with the Constant score [27,28] and the DASH (disabilities of the arm, shoulder and hand) questionnaire [29]. The Constant score is a test procedure with mixed weightings and is used as an instrument for the assessment of shoulder function.…”
Section: Methodsmentioning
confidence: 99%
“…Als niedriges Aktivitätslevel wurden Summenwerte von 0-5 festgelegt, als mittleres eines zwischen 6-10 Punkten, als ein hohes eines mit einem Punktwert von 11-20 und als sehr hoch mit Werten größer 20. Die Patienten erhielten zusätzlich einen Fragebogen mit modifiziertem Constant-Murley-Score (CS) als reliables und valides Selbstevaluations-Instrument [1,5].…”
Section: Introductionunclassified